FREQUENCY OF ALLERGIC BRONCHOPULMONARY ASPERGILLOSIS (ABPA) IN PATIENTS ADMITTED WITH ACUTE EXACERBATION OF ASTHMA IN A TERTIARY CARE HOSPITAL IN KARACHI: A PROSPECTIVE OBSERVATIONAL STUDY - ALI , W; KHAN , JA (Biological and Clinical Sciences Research Journal, 2024)
Allergic Bronchopulmonary Aspergillosis (ABPA) is a hypersensitivity reaction to Aspergillus species and often complicates the clinical course of asthma, leading to more severe exacerbations and poor disease control. Despite its clinical relevance, the prevalence of ABPA in asthma patients remains under-reported, especially in developing countries like Pakistan. Objective: This study aimed to determine the prevalence of ABPA among patients admitted with acute exacerbations of asthma at a tertiary care hospital in Karachi, Pakistan. Methods: A prospective observational quantitative study was conducted at the Department of Pulmonary Medicine, Aga Khan Hospital University Karachi, Pakistan from January 2023 to December 2023 in Karachi. The study included 150 isolated patients of either gender, aged between 18 and 80 years, with a clinical diagnosis of asthma or those eligible for spirometry. Data collected included demographic details, past medical history, pulmonary function test results, and serological data for ABPA diagnosis. The presence of ABPA was confirmed by elevated serum total IgE concentration, specific IgE to Aspergillus fumigatus, and radiological findings. Statistical analysis was conducted using SPSS, with p-values < 0.05 considered statistically significant. Results: The study revealed an overall prevalence of ABPA in 20% of the 150 patients with acute asthma exacerbations. Serum total IgE concentration was significantly higher in the ABPA group (450 IU/mL) compared to the non-ABPA group (p < 0.05). Additionally, patients with ABPA had significantly lower FEV1 (60% predicted) compared to those without ABPA (p < 0.05). Conclusion: The study highlights a notable prevalence of ABPA among asthma patients experiencing acute exacerbations. This underscores the importance of raising clinical awareness and implementing timely diagnostic strategies for ABPA in asthma management, which could significantly improve patient outcomes.